PERKAWINAN DINI DAN DAMPAKNYA TERHADAP PERLINDUNGAN ANAK DALAM HUKUM PERKAWINAN INDONESIA SEBAGAI TINJAUAN KOMPREHENSIF - Suryantoro, Dwi Dasa (LPPM STAI Muhammadiyah Probolinggo, 2025)
Early marriage in Indonesia remains a significant issue even though there has been a regulation that regulates the age limit for marriage through Law No. 16 of 2019. This study aims to examine the impact of early marriage on the rights of children, especially women, and evaluate the effectiveness of existing legal protections. The research method used is a qualitative approach with literature study and normative analysis of laws and regulations governing early marriage, especially Law No. 16 of 2019. The results of the study show that despite the age limit of marriage, the dispensation policy given by the religious court allows for early marriage. This has an impact on children's limited access to education, health, and economic opportunities. This study recommends the need to evaluate and strengthen dispensation policies and increase public awareness about the dangers of early marriage. Stricter policy changes and stricter oversight are needed to strengthen the protection of children's rights.